A SUGGESTION TO EVALUATION OF CIVIL ARCHITECTURE: BALIKESIR EXAMPLE - SEMERCİ, Fatih; BÜLÜÇ, Elif (International Journal of Engineering Technologies and Management Research, 2017)
Cities that reflect the characteristics of the era they have existed in have identities they possess that are created through social values and environmental data. One of the important factors in the formation of the identities of cities is buildings bearing historical heritage. The preservation and revitalization of these buildings bearing traces of the past is important for ensuring cultural continuity. Aim: These evaluation studies, which are essential in the context of conservation plans, are inevitable phases to determine the principles of the plans. Method: This study is aimed to propose a method for the architectural spatial and facade evaluation phase, which is essential before conservation decisions. The proposed method is based on a gradation system. Center district Balıkesir/Turkey is determined as the area to test this method. Result: It is proposed that this method explains the systematic way for evaluating architectural features belonging to historic sites whose conservation plans are to be prepared. In the study, traditional buildings are evaluated from the point of their exterior and interior architectural characteristics and classified as different value groups: A, B, C and D. This grouping will be advantageous to conservation decisions. Different technical teams may be organized to be responsible for these various value groups. Conclusion: a different approach for conservation in architecture. This will ensure accurate determination of programmatic work and cost estimates.